Effects of rapamycin on social interaction deficits and gene expression in mice exposed to valproic acid in utero - Kotajima-Murakami, Hiroko (Mol Brain, 2019)
The mammalian target of rapamycin (mTOR) signaling pathway plays a crucial role in cell metabolism, growth, and proliferation. The overactivation of mTOR has been implicated in the pathogenesis of syndromic autism spectrum disorder (ASD), such as tuberous sclerosis complex (TSC). Treatment with the mTOR inhibitor rapamycin improved social interaction deficits in mouse models of TSC. Prenatal exposure to valproic acid (VPA) increases the incidence of ASD. Rodent pups that are exposed to VPA in utero have been used as an animal model of ASD. Activation of the mTOR signaling pathway was recently observed in rodents that were exposed to VPA in utero, and rapamycin ameliorated social interaction deficits. The present study investigated the effect of rapamycin on social interaction deficits in both adolescence and adulthood, and gene expressions in mice that were exposed to VPA in utero. We subcutaneously injected 600 mg/kg VPA in pregnant mice on gestational day 12.5 and used the pups as a model of ASD. The pups were intraperitoneally injected with rapamycin or an equal volume of vehicle once daily for 2 consecutive days. The social interaction test was conducted in the offspring after the last rapamycin administration at 5–6 weeks of ages (adolescence) or 10–11 weeks of age (adulthood). Whole brains were collected after the social interaction test in the adulthood, and microarray and Western blot analyses were performed. Mice that were exposed to VPA and treated with vehicle exhibited a decrease in social interaction compared with control mice that were treated with vehicle. Rapamycin treatment in VPA-exposed mice improved social deficits. Mice that were exposed to VPA and treated with vehicle exhibited the aberrant expression of genes in the mTOR signaling pathway, and rapamycin treatment recovered changes in the expression of some genes, including Fyb and A330094K24Rik. Rapamycin treatment suppressed S6 phosphorylation in VPA-exposed mice. Aberrant gene expression was associated with social interaction deficits in VPA-exposed mice. Rapamycin may be an effective treatment for non-syndromic ASD in adolescent and adult patients who present impairments in the mTOR signaling pathway. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13041-018-0423-2) contains supplementary material, which is available to authorized users.